Significance of prediabetes as a nosological entity - Stepanek, Ladislav; Horakova, Dagmar; Nakladalova, Marie; Cibickova, Lubica; Karasek, David; Zadrazil, Josef (Biomedical papers, 2018)
Prediabetes is a glucose metabolism disorder considered as a distinct nosological entity which strongly predicts the development of type 2 diabetes mellitus. This nosological entity itself is a serious condition indicating an increased risk of atherosclerotic and oncological complications. In patients with prediabetes, other components of metabolic syndrome are usually present, such as arterial hypertension, obesity or dyslipidaemia, further increasing an individual's risk of morbidity and mortality. Prediabetes is a long-developing disorder which offers enough time for early diagnosis and intervention; it may even be reversible. This review summarizes current knowledge on the definition, detection, epidemiology, cardiovascular and other consequences of prediabetes. It also gives suggestions for future research, along with recommendations for clinical practice.
Keywords: prediabetes; impaired fasting glucose; impaired glucose tolerance; prevalence; cardiovascular complications; cancer